IMPLEMENTING COURSE SCHEDULE GENERATIONAPPLICATION FOR UNIVERSITY - Zhuniskhanov, M; Suliyev, R (Journal of Emerging Technologies and Computing, 2021)
This work is about researching and implementing СourseSchedule Generation Application for university. She compares other similarapplications in this area and explores important points. Through UML diagrams,important concepts and development progress are explained. Screenshots ofusing the application will also be provided. Dataset, configuration and rulesexplained. In the end, we will talk about the importance of such an applicationand facilitate planning for the university.